Effects of soil types on performance of septic tank/soil absorption system - Tran Yem; Nguyen, Cong Thanh; Samorn Muttamara; Chongrak Polprasert; Taiwan Power Company, R.O.C. (Bangkok : Asian Institute of Technology, 1981)
The treatment capacity of septic tank effluent on four different soil types was studied in controlled laboratory conditions, using four different soil columns. The columns were dosed with different hydraulic loadings depending upon the permeability of the soils used. Experimental results demonstrated that soil depth and soil type play an important role in determining the treatment capacity of effluent by soil. The upper zone of 30 cm depth was found to be very effective for COD, sus- pended solids, and nitrogen removal. Further increase in depth from 30 to 90 cm showed very less removal efficiency. The Thamuang clay loam and Rangsit topsoil silt loam showed better COD, suspended solids, nitrogen removal than Donmuang silt clay and Pattaya loamy sand. Both clay loam and topsoil silt loam yielded about 77 to 85% suspended solid removal at the depth 90 cm, whereas silt clay and loamy sand resulted in about 60 to 75% suspended solids at the same depth. About 70 to 85% COD and 64 to 75% nitrogen reductions were obtained in all soil columns at the depth of 90 and 150 cm. Physical, biological, and excessive hydraulic loading factors were identified as main factors of outlet and soil clogging.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1981
Keywords: Sewage -- Purification -- Rotating disc process